Experimental Analysis of Water Column Height and Air Flow Rate Effects on Two-Phase Airlift Pump Performance - Fidaroin, Arsyad Ni'am; Mujiarto, Sigit; Hayati, Nur; Saleh, Arif Rahman (FLYWHEEL : Jurnal Teknik Mesin Untirta, 2025)
This study experimentally investigates the effects of water column height and air flow rate on the performance of a two-phase airlift pump with a 15° injector angle. Two water column heights  and  and four air flow rates (30, 40, 50, and 60 LPM) were tested in a laboratory-scale setup. Efficiency was calculated using the Nicklin model, while effectiveness was determined based on the ratio of water to air mass flow rates. Flow patterns were recorded and analyzed using a high-speed camera. The results showed that increasing the water column height significantly improved both efficiency and effectiveness, with the highest values—12.270% and 2354.78, respectively achieved at  and 60 LPM. Flow pattern observations revealed that slug flow dominated at partial submergence, whereas churn flow became prevalent at full submergence with higher air flow rates. The findings demonstrate that optimizing submergence ratio, air flow rate, and injector configuration is essential for achieving high-performance and energy-efficient airlift pump operation.